Progress of MRI Radiomics in Hepatocellular Carcinoma - Gong, Xue-Qin; Tao, Yun-Yun; Wu, Yao–Kun; Liu, Ning; Yu, Xi; Wang, Ran; Zheng, Jing; Liu, Nian; Huang, Xiao-Hua; Li, Jing-Dong; Yang, Gang; Wei, Xiao-Qin; et al. (Frontiers in Oncology, 2021)
Background: Hepatocellular carcinoma (HCC) is the sixth-most common cancer in the world and the third-leading cause of cancer-related death. Although the diagnostic scheme of HCC is being perfected, the prognosis of HCC is still not satisfactory. In addition to factors such as the size and number of tumors and vascular invasion displayed by traditional imaging, some clinicopathological features and gene expression parameters are also important in the prognosis of HCC patients. However, most parameters are based on postoperative pathological examinations, which cannot help with preoperative decision-making. As a new field, radiomics extracts high-throughput imaging data from different types of images to build models and predict clinical outcomes in a noninvasive way before surgery, making it a powerful aid for making personalized treatment decisions before surgery. Objective: This study reviewed the workflow of radiomics and the research progress on magnetic resonance imaging (MRI) radiomics in the diagnosis and treatment of HCC. Methods: Eligible articles published before February 22, 2021 were retrieved through PubMed. The search keywords included HCC, MRI, radiomics, diagnosis, histopathology, microvascular invasion, radiomics, relapse, trans-arterial chemoembolization, targeted therapy, immunotherapy, therapeutic response, and prognosis. Results: The radiomic features of MRI can be used as biomarkers for the differential diagnosis, histological grading, microvascular invasion, gene expression, local and systemic therapeutic response, and prognosis of HCC patients. Conclusion: Radiomics is a promising new imaging method. MRI radiomics has high application value in the diagnosis and treatment of HCC.